Green Practices: Revealing the Role of Pro-Environmental Behavior Mediation in Hotel Performance - Widagdo, C Susmono; Guritno, Bambang -; Prayogi, Refal -; Anggraeni, Kamelita -; Palupiningtyas, Dyah - (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the effects of competence, pro-environmental conduct, and pro-environmental behavior as a mediator on hotel employee performance. Hotel Oak Tree Semarang, a green hotel, hosted the probe. Quantitative survey methods were used. Purposive sampling selected 109 employees for the research. Data were evaluated using AMOS 24's SEM. The results show that competence and pro-environmental behavior boost employee performance. Environmentalism also moderates the effect of competence on employee performance. These findings expand green human resource management (GHRM) and have practical implications for hotel managers seeking to increase employee performance and encourage environmentally friendly practises.